The Compilation and Execution of a Measurement of Chinese Undergraduates’ Moral Values Approval - Zhu, Hai-Long (ETHICS IN PROGRESS, 2015)
The study completes the compilation of the questionnaire on Chinese undergraduates’ moral values from six moral values dimensions: honesty and compliance, civility and self-discipline, love, unity and be helpful, esteem and filial respect. The questionnaire has 31 questions in all, taking advantage of Likert scale. Using this scale, its alpha reliability reach 0.887 with clear internal structure. The validity is well and the model fitting index accords with statistical measurement, which covers the shortage of empirical study on Chinese undergraduate students’ moral values. The measurement, which focused undergraduate moral values, is compiled by a total of 768 valid samples from 6 colleges. Measurement results show that there are sequences of orientation on Chinese undergraduates’ moral values approval, and the order is: Honesty and compliance, civility and discipline, filial respect unity and be helpful, love and esteem; while gender differences do exist. The male undergraduates’ identity level of honesty and compliance, civility and self-discipline, love, and filial respect ranks higher than that of female undergraduates; however, the differences, between male and female undergraduates, on unity and being helpful, as well as esteem are not significant.